EDUCAÇÃO E AUTORITARISMO: A FORMAÇÃO HUMANA ORIENTADA PARA A REPRODUÇÃO IDEOLÓGICA E PARA O MERCADO DE TRABALHO NA EDUCAÇÃO BÁSICA NOS CONTEXTOS DO ESTADO NOVO E DA DITADURA CIVIL-MILITAR - Lins, Michel Francisco (2022)
The research approaches the idealization of man in the formation of the Brazilian citizen in the context of the authoritarian State and the relations between labor and education that guide the discussions before the organization of the capitalist school. The study goes through the Estado Novo (1937-1945) and the Civil-Military Dictatorship (1964-1985) periods. The dissertation uses this historical floor to counteract the idealizations and distortions of capitalist society in the relationship between labor and institutionalized education (school). What runs through the historiographical analysis of this dissertation are the capitalist economical needs imposed on the formal educational process according to the periods discussed. It describes the organizations of the Estado Novo before of the construction of a public school with an economistic bias and the idealization of a “new” man seeking to build a “Brazilianness” through institutionalized education. The study points out the idealizations of the Civil-Military Dictatorship before of the technical training process, this means training for the labor market, in which it reinforces its bourgeois hegemony along with the theory of human capital. It presents a pedagogy, a conception of man, labor and counter-hegemonic education from the Historical-Critical Pedagogy aiming to ground a revolutionary práxis that is capable of fighting against discourses, idealizations, education, labor and conceptions of man that legitimize authoritarian thoughts and States.